PENERAPAN E-LEARNING DALAM PEMBELAJARAN DARING DI PRODI MANAJEMEN PENDIDIKAN ISLAM FAKULTAS ILMU TARBIYAH DAN KEGURUAN PADA MASA PANDEMI COVID-19 - Ainur Rahman; Sedya Santosa; Nora Saiva Jannana (STAI Ma'had Aly Al-Hikam Malang, 2022)
During the covid-19 pandemic, new rules in the world of education have started, namely the shift of a learning process form face to face to online. Therefore, the researcher aims to find out what e-lear ing media are widely used in the online learning process and the advantages and disadvantages of learning in the Islamic Education Management Study Program, Faculty of Tarbiyah and Teacher Training at UIN Sunan Kalijaga Yogyakarta. This study uses a qualitative descriptive approach. Google classroom and whatsapp are online learning media that are quite in demand by users, both as the only media or as supporting media. The advantages of implementing e-learning are that students become independent, flexible, save on stationery, and students become active. The drawbacks of implementing e-learning are that the interaction between lecturers and students becomes more distant, students who do not have the motivation to learn tend to fail, limited internet access, and the teaching and learning process tends towards training rather than education.